Government Size and Digital Inequality in Indonesia - Anna Yulianita; Subardin Subardin; Zulfikri Zulfikri (Goodwood Publishing, 2024)
Purpose: This study aims to analyze the impact of government size in the field of infrastructure on digital inequality in Indonesia. Research Methodology: This study uses panel data analysis with the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM) approaches using research samples from the Central Bureau of Statistics, Ministry of Finance, and International Telecommunication Union in Indonesia. Results: The results indicate that government-sized infrastructure has a negative and significant effect on the Information and Communication Technology (ICT) Index, while the square government-sized infrastructure or infrastructure expenditure optimization effect has a positive and significant impact on the ICT Index, and the implementation of the infrastructure budget supports digital equity. Conclusions: This study examines the impact of government size on digital inequality in Indonesia at the regional level, using data from 2016–2020. The results show that a smaller government size has a positive impact on the ICT Index, while a larger government size leads to a negative, nonlinear effect on regional ICT indices. Limitation: This study was limited to the national level of each region in Indonesia. Contributions: This study aims to serve as a reference for government considerations in strategic policies related to infrastructure spending and issues of the technology change strategy. Novelty: This study contributes to the existing literature by exploring the critical role of government spending on infrastructure in bridging the digital divide in Indonesia, with a particular focus on digital infrastructure.